Favorable prognosis in pediatric brainstem low‐grade glioma: Report from the German SIOP‐LGG 2004 cohort. Issue 12 (27th November 2019) - Holzapfel, Johannes; Kandels, Daniela; Schmidt, René; Pietsch, Torsten; Warmuth‐Metz, Monika; Bison, Brigitte; Krauss, Jüergen; Kortmann, Rolf‐Dieter; Timmermann, Beate; Thomale, Ulrich‐Wilhelm; Albert, Michael H.; Hernáiz Driever, Pablo; et al.
Abstract : Reports on pediatric low‐grade glioma (LGG) of the caudal brainstem are retrospective with heterogeneous cohorts, variable treatments and inconsistent outcome data. We analyzed their natural history and asked whether brainstem location proved unfavorable for survival within the framework of the comprehensive SIOP‐LGG 2004 management strategy. Within the prospectively registered, population‐based German SIOP‐LGG 2004 cohort 116 patients (age 0.2–16.5 years, 10% Neurofibromatosis NF1) were diagnosed with LGG of the pons (27%) and medulla oblongata (73%). After biopsy (23%), variable resection (63%) or radiologic diagnosis only (14%), 59 patients received no adjuvant treatment. Radiologic progression or severe neurologic symptoms prompted chemo‐ ( n = 39) or radiotherapy ( n = 18). After further progression (28/57), salvage treatments included multiple treatment lines for 12/28 patients. Five‐years event‐free survival dropped to 0.40, while 5‐years overall survival was 0.95 (median observation time 6.8 years). Higher extent of resection yielded lower progression rate ( p = 0.001), but at a cost of 21/100 patients suffering from new postsurgical complications including respiratory insufficiency. Central review confirmed pilocytic astrocytoma (56%), diffuse astrocytoma (8%) or glioneuronal histology (16%) (others 4%, no histology 17%). Malignant evolution was documented in five patients associated with Histone3 mutation in 2/5. Our treatment algorithm conveyed high overall survival for pediatric brainstem LGG. Extensive neurosurgical resection did increase additional postoperative neurologic deficits but not overall survival in this often‐chronic disease. More than half of all patients can be safely followed by observation, while multimodal adjuvant treatment can control progressive tumors. Molecular assessment should confirm low‐grade diagnosis and may detect patterns prognostic for malignant evolution. Abstract : What's new? Outcome studies for pediatric low‐grade gliomas (LGG) of the brainstem have generally been small and of low quality, making it difficult to determine prognosis. In this prospective, multicenter study, the authors developed a detailed description of the natural history, treatment response, and prognostic factors associated with favorable survival when a comprehensive treatment strategy was used. This treatment algorithm resulted in high overall survival for pediatric brainstem LGG. The study also emphasizes the importance of the predictive value of molecular patterns, as malignant evolution can occur even in low‐grade tumors.